2005
DOI: 10.1073/pnas.0506124102
|View full text |Cite
|
Sign up to set email alerts
|

Specificity versus stability in computational protein design

Abstract: Protein-protein interactions can be designed computationally by using positive strategies that maximize the stability of the desired structure and͞or by negative strategies that seek to destabilize competing states. Here, we compare the efficacy of these methods in reengineering a protein homodimer into a heterodimer. The stability-design protein (positive design only) was experimentally more stable than the specificity-design heterodimer (positive and negative design). By contrast, only the specificity-design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 38 publications
5
123
0
Order By: Relevance
“…Several computational approaches have shown that novel enzyme specificities can be generated through redesign of the dimer interface [19][20][21] . We employed 3D protein modeling based on the published crystal structures of FokI 22,23 followed by computational analysis of dimerization to identify amino acids at the interface that adjust dimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…Several computational approaches have shown that novel enzyme specificities can be generated through redesign of the dimer interface [19][20][21] . We employed 3D protein modeling based on the published crystal structures of FokI 22,23 followed by computational analysis of dimerization to identify amino acids at the interface that adjust dimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has addressed many problems related to the design of improved protein-protein binding affinity, such as the design of stable protein folds 2-4 , binding pockets for peptides and small molecules [5][6][7] , altered protein-protein specificity [8][9][10][11][12] , and altered enzymatic activity [13][14][15] . The design of improved antigen-binding affinity has met with limited success, however [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have emphasized the modular design of binding sites, with energetic cooperative contribution of single residues within the module; and additive between modules [23][24][25]. Computational protein design methods have also been used to elucidate the tradeoff between stability and specificity for the optimization of biological function [8,26]. However, most of these studies have been carried out on a limited set of protein examples, while the general principles governing protein-protein binding remain elusive (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%